The relationship between psychiatric symptom severity and quality of life in patients with beta-thalassemia major: North Cyprus experience - Tuzmen, Sukru; Ozsat, Kubra; Isiktas, Serdal; Senol, Hulya (Springernature, 2024)
[Abstract Not Available]
56th Annual Conference of the European-Society-of-Human-Genetics (ESHG) -- JUN 10-13, 2023 -- Glasgow, SCOTLAND